Pengaruh Emotional Branding Lagu "Nina" oleh .Feast terhadap Brand Attachment dan Loyalitas Fanbase Kelelawar Semarang - Hega Satriya Hutama; Mubarok Mubarok (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study is motivated by the empirical problem regarding the image shift of the music group .Feast, from aggressive social critique narratives to a more personal and emotional tone through the song "Nina". This extreme shift risks triggering the loss of loyalty from old fans. Therefore, this study aims to examine and analyze the effect of optical emotional branding in the song "Nina" on brand attachment and fan loyalty in the Kelelawar Semarang regional fanbase. This research employs an explanatory quantitative method using the S-O-R (Stimulus-Organism-Response) Theory approach. Data were collected through distributing questionnaires to 100 respondents who are official members of the Kelelawar Semarang fanbase, selected using a purposive sampling technique. Data analysis was conducted using Path Analysis with the assistance of the IBM SPSS program. The results of the study prove that: (1) Emotional Branding has a positive and significant effect on Brand Attachment; (2) Emotional Branding does not have a significant direct effect on Fan Loyalty; (3) Brand Attachment has a positive and significant effect on Fan Loyalty; and (4) There is a significant indirect effect of Emotional Branding on Fan Loyalty through Brand Attachment. The conclusion of this study confirms the occurrence of a Full Mediation phenomenon. This indicates that the emotional value of a song cannot instantly create fan loyalty, but absolutely must foster inner closeness (brand attachment) first as a bridge. As a recommendation, musicians and music industry practitioners are advised to not merely sell audio quality, but to design works that possess personal relevance and empathy in order to secure the long-term loyalty of their listeners.